An anti-windup design for polytopic systems by a parameter-dependent Lyapunov function approach - Yong-Yan Cao; Zongli Lin (2005 International Conference on Control and Automation, 2005)
This paper presents an anti-windup compensation design for polytopic systems. A parameter-dependent Lyapunov function approach is first proposed to reduce the conservatism in estimating the performance of the closed-loop system under a given anti-windup design. An iterative algorithm is then proposed to design the anti-windup compensation gain. Numerical examples demonstrate the effectiveness of the proposed design approach.